Integrated marketing communication strategy towards brand awareness of product telkomsel digital lifestyle; case study of platform streaming langit musik - Afifah Handoyo, Nadya; Furinto, Asnan (The Indonesian Journal of Business Administration, 2019)
Abstract – Telkomsel has established itself as the leading cellular operator in Indonesia, with more than 196 million customers, and more than 160,000 BTS operating in 11 regions across Indonesia, with more than 5,400 employees registered. This study examines how well-known their brand awareness is based on surveys conducted by the authors. This topic was chosen because of the company's business problems, where companies want to know how well their brand awareness is. In the end, this research is expected to be able to provide a recommended strategy based on the conditions and results of the surveys that have been conducted to conduct research. In addition, there are several problems faced by companies, namely they want to know what their customers feel when they know the products offered. Then in the paper study, the authors also examine what should be the recommended strategy for their long term goals, but this will not be the point of emphasis of the paper and still need further surveys to carry out the strategies that will be recommended to the company. Keywords: marketing communication, brand awarness